Good News or Bad News? How Message Framing Influences Consumers’ Willingness to Buy Green Products - Tong, Zelin; Liu, Diyi; Ma, Fang; Xu, Xiaobing (Frontiers in Psychology, 2021)
Despite the growing social interest in green products, companies often find it difficult to find effective strategies to induce consumers to purchase green products or engage in other environmentally friendly behaviors. To address this situation, we examined the favorable or unfavorable effects of positive and negative message frames on consumers’ willingness to consume green products in different psychological distance contexts. Through two Studies, we found that the positive information framework played a more pronounced role in context when consumers were in closer spatial distances. More importantly, we found that the emotional factors of fear and hope were intrinsic causes of this phenomenon. Correspondingly, the negative information framework played a better facilitating role in context with farther spatial distance, while shame and pride were the emotions responsible for this effect. Finally, we discuss the theoretical and managerial implications of our work, as well as its limitations and future research directions.